Comparison of Social Media as a Platform for Financial Literacy Source - Wahyu Fahrul Ridho (Jurnal Aplikasi Manajemen dan Bisnis, 2022)
Financial literacy has been an essential aspect of financial inclusion. One of the recently explored drivers of financial literacy is social media. Social media has occupied most of the user's attention and thus become one of the primary sources of knowledge in modern society. This study purpose was to examine the context of social media in applying financial literacy planning and program. This study is descriptive by using a structured literature review approach to address social media in the context of financial literacy and distinguish h category of social media and its attribute regarding the application of financial literacy. This study found that social media has been categorized to put perspective on its usefulness as a financial literacy program platform. Every social media category has different uses; some are better suited for a specific financial literacy program. This study’s limitation was that it does not measure the effectiveness of the financial literacy program based on its social media platform. However, this study contributes to researchers and practitioners to better understand the dynamic of the financial literacy program through social media platforms.